A quasilinear singular elliptic problem related to the Kardar–Parisi–Zhang equation. Issue 5 (4th April 2021) - Boccardo, Lucio; Orsina, Luigi; Peral, Ireneo
ABSTRACT: In this paper, we will study existence and properties of solutions for the nonlinear Dirichlet problem − div ⁡ ( M ( x ) ∇ u ) = b ( x ) | ∇ u | u θ + f ( x ), in  Ω, u = 0, on  ∂ Ω, where Ω ⊂ R N is a bounded domain, 0 < θ ≤ 1, M is a uniformly elliptic and bounded matrix, and b, f are functions in some Lebesgue spaces.